1997
DOI: 10.1021/ma970647c
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Development in Alkyl-Substituted Semiflexible Polymers

Abstract: Nonsymmetrically substituted semiflexible polymers were synthesized by reacting (hydroxypropyl)cellulose (HPC) with hexyl, octyl, dodecyl, and octadecyl isocyanates. X-ray diffraction studies indicate that the polymer chains are assembled in regular, layered arrays. Polymers with six and eight carbons in the side chains (C6HPC and C8HPC) showed spherulitic structures typical of common crystalline polymers when examined by a polarized optical microscope (POM), whereas liquid crystalline (LC) textures were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In fact, layered structures of the type described above were found for several semi-flexible polymers. Lee et al [17] used a similar model to describe the structure of several derivatives of HPC with various side chain length, according to Wegners bilayer model for substituted aromatic polyesters. [18] Gray et al reported a parallel alignment of the polymer backbone in thermotropic cholesteric phases of HPC esters.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, layered structures of the type described above were found for several semi-flexible polymers. Lee et al [17] used a similar model to describe the structure of several derivatives of HPC with various side chain length, according to Wegners bilayer model for substituted aromatic polyesters. [18] Gray et al reported a parallel alignment of the polymer backbone in thermotropic cholesteric phases of HPC esters.…”
Section: Resultsmentioning
confidence: 99%
“…Alkane molecules with their simple, rod-like molecular shape are a model system for more complex chainlike organic molecules [5][6][7] and are also important building blocks, e.g., as side chains of polymers and can dominate their crystallisation behavior. 8,9 Beyond its importance as a generic model system for fundamental molecular processes, tetratetracontane (TTC), in particular, is also of technological importance in organic electronics as an encapsulation material for transistors and biosensors in an aqueous environment, 10,11 where the active layer is completely wetted by TTC and therefore fully encapsulated.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization within the alkyl nanodomains of comb-like polymers occurs when the number of carbon atoms of the side chain is 12 or more, as in the cases of some alkyl-substituted rigid polymers, [23][24][25][26][27][28][29][30][31][32] exible polymers [33][34][35][36] and semi-exible polymers. 37,38 The crystallizable CH 2 units are usually packed into a hexagonal lattice, 39,40 but some other packing modes of the CH 2 units (for example, orthorhombic packing) have been reported for side chain polymers with long alkyl groups. [41][42][43][44] In addition, transitions between hexagonal and orthorhombic packing can also occur under certain conditions.…”
Section: Introductionmentioning
confidence: 99%